👤

A. 4x + 1 = 2x + 7
B. 3x + 5 = x +15
C. 6x + 7 = 5x +13
D. 10x - 6 = 7x + 9
E. 5x – 1 = 2x + 11
F. 8 = 2
6
8
G. 11 = 2
H. b - 11 = 11
I. 5z = 4
J. 5 = 9s
pa help naman po plsss​


Sagot :

Answer:

ANSWER

\begin{gathered} \\ \\ \end{gathered}

A. 4x+1 = 2x+7

\begin{gathered} \\ 4x - 2x = 7 - 1 \\ 2x = 6 \\ \frac{2x}{2} = \frac{6}{2} \\ \frac{ \cancel2x}{ \cancel2} = \frac{6}{2} \\ \\ \boxed{x = 3} \\ \\ \end{gathered}

4x−2x=7−1

2x=6

2

2x

=

2

6

2

2

x

=

2

6

x=3

B. 3x+5 = x+15

\begin{gathered} \\ 3x - x = 15 - 5 \\ 2x = 10 \\ \frac{2x}{2} = \frac{10}{2} \\ \frac{ \cancel2x}{ \cancel2} = \frac{10}{2} \\ \\ \boxed{x = 5} \\ \\ \end{gathered}

3x−x=15−5

2x=10

2

2x

=

2

10

2

2

x

=

2

10

x=5

C. 6x+7 = 5x+13

\begin{gathered} \\ 6x - 5x = 13 - 7 \\ \\ \boxed{x = 6} \\ \\ \end{gathered}

6x−5x=13−7

x=6

D. 10x-6 = 7x+9

\begin{gathered} \\ 10x - 7x = 9 + 6 \\ 3x = 15 \\ \frac{3x}{3} = \frac{15}{3} \\ \frac{ \cancel{3}x}{ \cancel3} = \frac{15}{3} \\ \\ \boxed{x = 5} \\ \\ \end{gathered}

10x−7x=9+6

3x=15

3

3x

=

3

15

3

3

x

=

3

15

x=5

E. 5x-1 = 2x+11

\begin{gathered} \\ 5x - 2x = 11 + 1 \\ 3x = 12 \\ \frac{3x}{3} = \frac{12}{3} \\ \frac{ \cancel3x}{ \cancel3} = \frac{12}{3} \\ \\ \boxed{x = 4} \\ \\ \end{gathered}

5x−2x=11+1

3x=12

3

3x

=

3

12

3

3

x

=

3

12

x=4

F. 8 = z/6

\begin{gathered} \\ 8 = \frac{z}{6} \\ (6)(8) = \frac{z}{6} (6) \\ (6)(8) = \frac{z}{ \cancel6} ( \cancel6) \\ \\ \boxed{z = 48} \\ \\ \end{gathered}

8=

6

z

(6)(8)=

6

z

(6)

(6)(8)=

6

z

(

6

)

z=48

G. 11 = x/8

\begin{gathered} \\ 11 = \frac{x}{8} \\ (8)(11) = \frac{x}{8} (8) \\ (8)(11) = \frac{x}{ \cancel8} ( \cancel8) \\ \\ \boxed{x = 88} \\ \\ \end{gathered}

11=

8

x

(8)(11)=

8

x

(8)

(8)(11)=

8

x

(

8

)

x=88

H. b-11 = 11

\begin{gathered} \\ b - 11 = 11 \\ b = 11 + 11 \\ \\ \boxed{b = 22} \\ \\ \end{gathered}

b−11=11

b=11+11

b=22

I. 5z = 4

\begin{gathered} \\ 5z = 4 \\ \frac{5z}{5} = \frac{4}{5} \\ \frac{ \cancel5z}{ \cancel5} =\frac{4}{5} \\ \\ \boxed{z = \frac{4}{5} } \\ \\ \end{gathered}

5z=4

5

5z

=

5

4

5

5

z

=

5

4

z=

5

4

J. 5 = 9s

\begin{gathered} \\ 5 = 9s \\ \frac{5}{9} = \frac{9s}{9} \\ \frac{5}{9} = \frac{ \cancel9s}{ \cancel9} \\ \\ \boxed{s = \frac{5}{9}} \\ \\ \\ \end{gathered}

5=9s

9

5

=

9

9s

9

5

=

9

9

s

s=

9

5

Step-by-step explanation:

hope its help its not my answer but

hope its help